The Application of Nesting Therapy on Thermoregulation Changes in Premature Infants in the NICU - Afifah, Marlia; Fadila, Erida (INDOGENIUS, 2025)
Background & Objective: A preterm infant is defined as a baby born before 37 weeks of gestation (Kemenkes, RI, 2024). The World Health Organization (WHO), 2023 , categorizes preterm births based on gestational age: ≤28 weeks is extremely preterm, ≤32 weeks is very preterm, and 37 weeks is moderately preterm. According to (Kemenkes, RI, 2024), the WHO estimates that 13.4 million babies were born prematurely in 2020. Indonesia ranks fifth highest in the world for premature births, with approximately 657,700 cases. One of the issues faced by premature infants is metabolic disorders, where premature infants are at risk of experiencing a decrease in body temperature due to low body fat reserves and incomplete brain maturation in regulating the infant's body temperature (Rufaindah et al., 2022). The objective is to analyze the effect of nesting therapy on changes in thermoregulation in premature infants in the NICU of Kardinah General Hospital, Tegal City. Method: descriptive study using case study results with a nursing care process approach. Instruments: pediatric nursing care format, digital thermometer. Result: The application of nesting therapy for three days on premature infants with hypothermia resulted in changes in body temperature within the normal range for premature infants. Conclusion: Nesting therapy is effective in increasing body temperature in premature infants, as their minimal movement contributes to energy conservation. This study is expected to enhance the application of developmental care, particularly in premature infants.